2021
DOI: 10.1097/ju.0000000000001954.14
|View full text |Cite
|
Sign up to set email alerts
|

Mp09-14 en-Bloc Enucleation Technique Using Moses Laser (En-Bloc Molep) vs en-Bloc Holep: Comparing Intra and Post-Operative Outcomes for en-Bloc Enucleation Technique With Early Apical Release, to Treat Patients Affected by Benign Prostatic Enlargement (Bpe)

Abstract: re-catheterizations than RASP (p[0.0294). Three-month PSA was similar in both arms. There was a significant difference in voiding symptoms at 3 months with IPSS [ 2 in the HoLEP arm and IPSS [ 7 (p <0.001) in the RASP arm, mainly irritative LUTS.CONCLUSIONS: Both HoLEP and RASP are feasible and safe procedures for prostatomegaly >100 cc. HoLEP is associated with significantly lesser duration of surgery, post-operative indwelling catheter and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(19 citation statements)
references
References 0 publications
8
11
0
Order By: Relevance
“…OT was reported in six studies 4,6–8,14,15 (277 MoLEP vs. 336 HoLEP). Study heterogeneity was relatively pronounced ( I 2 = 73.3%, p = 0.002), and a random‐effects model was used to analyze the data, which showed that the MoLEP group had a significantly shorter mean OT than the HoLEP group, with a statistically significant difference (WMD = −15.02 min, 95% CI [−20.50, − 9.53], p < 0.001) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…OT was reported in six studies 4,6–8,14,15 (277 MoLEP vs. 336 HoLEP). Study heterogeneity was relatively pronounced ( I 2 = 73.3%, p = 0.002), and a random‐effects model was used to analyze the data, which showed that the MoLEP group had a significantly shorter mean OT than the HoLEP group, with a statistically significant difference (WMD = −15.02 min, 95% CI [−20.50, − 9.53], p < 0.001) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…After a full‐text reading of the remaining 46 articles, 34 that did not meet the inclusion criteria were excluded. Twelve studies were finally included in this meta‐analysis 4–8,10,14–19 . The literature search flow and results are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations